A BIOEQUIVALENCE STUDY OF AMPICILLIN (GENERIC PRODUCTS) IN RABBITS - Wahyono, Djoko; ., Nurlaila (INDONESIAN JOURNAL OF PHARMACY, 2001)
The use of generic medicine in health services has strongly been suggested by government. Production of those type of medicine by government appointed pharmaceutical manufacturers has shown a good progress. However, monitoring to those products in the market, based on the bioequivalence quality, still need to be improved. An example of medicine produced in generic form is Ampicillin, one of the broad spectrum antibiotic effective to treat upper respiratory tract infections. The aim of this research was to evaluate the bioavailability of generic ampicillin capsules (500 mg) compared to the patented product. The research was carried out as follow: six male rabbits weighing 2.0 - 2.5 kg were assigned to a cross - over design to receive both products orally after 24 hour fasting. The generic and patented products were given to the rabbits with a week wash-out period. Following drug administration, the blood samples (11 samples) were drawn from the marginal ear vein at designated time (5-330 minutes) to analyse unmetabolized ampicillin fluorometrically. Detection of the ampicillin was recorded at maximum excitation (350 nm) and maximum emission (420 nm) wavelengths. The result showed that the AUC value of the generic product (3,211.25 Â± 635.23 ïg hour/ml) was significantly higher than that of patented product (2,425.68 Â± 895.26 ïg hour/ml) (p<0.05). The peak level of ampicillin (Cmax) was significantly higher for the generic (17.00 Â± 5.10 ïg/ml) than patented product (11.25 Â± 2.75 ïg/ml), while time to reach Cmax was not significantly different between the two products, ie. 77.34 Â± 16.70 minutes (generic) and 82.48 Â± 13.57 minutes (patented). The study concluded that the ampicillin capsules in generic form had a better biovailability than patented product. Key words: ampicillin, generic product, bioequivalence